2017
DOI: 10.1038/nature24283
|View full text |Cite
|
Sign up to set email alerts
|

Reversing SKI–SMAD4-mediated suppression is essential for TH17 cell differentiation

Abstract: Th17 cells are critically involved in host defense, inflammation, and autoimmunity1–5. TGF-β is instrumental in Th17 differentiation by cooperating with IL-66,7. Yet, the mechanism of how TGF-β enables Th17 differentiation remains elusive. Here we reveal that TGF-β licenses Th17 differentiation by releasing Ski-Smad4-complex suppressed RORγt expression. We found serendipitously that, unlike wild-type T cells, Smad4-deficient T cells differentiated into Th17 cells in the absence of TGF-β signaling in a RORγt-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
101
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(110 citation statements)
references
References 30 publications
6
101
3
Order By: Relevance
“…MSCs can differentiate into osteoblasts and adipocytes, and the differentiation into either cell type is reversely exclusive . In this study, we demonstrate a noncanonical role of Smad4 independent of TGF‐β and BMP signals regarding MSC differentiation, like TGF‐β‐independent functions of Smad4 reported by several groups . Our work revealed that Smad4 is reciprocally involved in osteogenic and adipogenic differentiation in C3H10T1/2 MSC cell line and primary hASCs and modulates the nuclear localization of Taz in all cells used in this study.…”
Section: Discussionsupporting
confidence: 78%
“…MSCs can differentiate into osteoblasts and adipocytes, and the differentiation into either cell type is reversely exclusive . In this study, we demonstrate a noncanonical role of Smad4 independent of TGF‐β and BMP signals regarding MSC differentiation, like TGF‐β‐independent functions of Smad4 reported by several groups . Our work revealed that Smad4 is reciprocally involved in osteogenic and adipogenic differentiation in C3H10T1/2 MSC cell line and primary hASCs and modulates the nuclear localization of Taz in all cells used in this study.…”
Section: Discussionsupporting
confidence: 78%
“…TGF-β signaling reverses Smad4-mediated suppression of RORγt via a SKI-dependent mechanism. 147 Whether similar mechanisms are underlying TGF-β-induced T RM differentiation remains to be demonstrated. In addition, TGF-β regulates several T cell-related target genes (e.g., Eomes and RORγt) in a Smad2/3-independent manner.…”
Section: Transcriptional Regulation Of Trm Cellsmentioning
confidence: 99%
“…For example, genetic repression of TH1 and TH2 cell differentiation was shown to relieve the requirement for TGF-b in IL-6-mediated TH17 induction and, indeed, TH17 cells can be differentiated in vitro by a combination of IL-6, IL-23 and IL-1β (Das et al, 2009;Ghoreschi et al, 2010). Recently, Wan and colleagues revealed that SKI, via SMAD4, transcriptionally repressed Rorc and that TGF-β signaling degraded or modified SKI to relieve the inhibition and promote TH17 cell differentiation in the presence of IL-6 (Zhang et al, 2017). Our studies indicate that SAAs function independently of STAT3 or the SMAD transcription factors, and that they do not regulate SKI degradation (unpublished).…”
Section: Saa-dependent Differentiation Of Pathogenic Th17 Cellsmentioning
confidence: 99%